2018
DOI: 10.1111/cge.13259
|View full text |Cite
|
Sign up to set email alerts
|

Systematic reanalysis of genomic data improves quality of variant interpretation

Abstract: As genomic sequencing expands, so does our knowledge of the link between genetic variation and disease. Deeper catalogs of variant frequencies improve identification of benign variants, while sequencing affected individuals reveals disease-associated variation. Accumulation of human genetic data thus makes reanalysis a means to maximize the benefits of clinical sequencing. We implemented pipelines to systematically reassess sequencing data from 494 individuals with developmental disability. Reanalysis yielded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
2
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 20 publications
0
46
2
2
Order By: Relevance
“…While the proband is unaffected by myoclonus, it could be hypothesized that the mechanistically distinct, mosaic loss-of-function observed in this case could elicit a unique effect with relevance the observed phenotype. Ultimately however, either functional validation studies or further patient-based analyses are necessary to draw any conclusion and SAMD12 represents a gene whose functional links should be flagged for future systematic reanalysis (Hiatt et al, 2018;Wenger, Guturu, Bernstein, & Bejerano, 2017). A further consideration is the clinically reported 16p13.3 deletion and corresponding detection of a PDPK1-PRSS21 fusion transcript.…”
Section: Discussionmentioning
confidence: 99%
“…While the proband is unaffected by myoclonus, it could be hypothesized that the mechanistically distinct, mosaic loss-of-function observed in this case could elicit a unique effect with relevance the observed phenotype. Ultimately however, either functional validation studies or further patient-based analyses are necessary to draw any conclusion and SAMD12 represents a gene whose functional links should be flagged for future systematic reanalysis (Hiatt et al, 2018;Wenger, Guturu, Bernstein, & Bejerano, 2017). A further consideration is the clinically reported 16p13.3 deletion and corresponding detection of a PDPK1-PRSS21 fusion transcript.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of these difficulties, pioneer studies have showed the interest of srGS as a diagnostic tool in DA/ID, resulting in a positive yield of around 30% in individuals with previous negative ES results or as a first-line molecular test. [41][42][43] As for ES, periodic reanalysis of srGS data, in light of new scientific knowledge, will further increase diagnostic rate (~10%) [44][45][46] in clinical settings is to be restricted to Mendelian disease-causing genes. 15 Therefore, it is crucial to keep any bioinformatics pipeline upto-date with the available literature.…”
Section: Short-read Genome Sequencingmentioning
confidence: 99%
“…Genetic alterations of which the clinical significance is still unclear today may be classified in the future as definitely pathogenic or benign. The possibility of reanalysis is a big advantage of DNA sequencing, maximizing its benefit for clinical care . Current literature on (whether, and to what extent there is an obligation for) genetic reanalysis is focused on the CG context using WES/WGS.…”
Section: Postanalytical Considerations: Reporting Storing and Reusimentioning
confidence: 99%
“…benefit for clinical care [68,69] . Current literature on (whether, and to what extent there is an obligation for) genetic reanalysis is focused on the CG context using WES/WGS.…”
Section: S Vos Et Almentioning
confidence: 99%